A tale of two membranes: from poly (ionic liquid) to metal–organic framework hybrid nanoporous membranes via pseudomorphic replacement. Issue 4 (5th June 2017) - Sun, Jian-Ke; Lin, Hui-Juan; Zhang, Wei-Yi; Gao, Min-Rui; Antonietti, Markus; Yuan, Jiayin
Abstract : A general method to produce a variety of free-standing asymmetric MOF hybrid membranes and superstructure arrays on different substrates was developed. Abstract : A general approach to produce a variety of free-standing asymmetric MOF hybrid membranes and superstructure arrays on "inert" substrates with tailored crystal sizes and shapes was developed. The obtained MOF hybrid membrane exhibits fast actuation in response to external gas stimulus.